Contestation of Meanings in Procedural Democracy: Inter-Media Framing of President Prabowo’s Dialogue with Journalists - Joan Imanuel Edon; Ira Mirawati; Zidan Abdurrahman; Aditya Anggara R.B. (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study analyzes how Indonesian national media framed President Prabowo Subianto’s dialogue with seven senior journalists held in Hambalang on April 6, 2025, a moment positioned as a symbol of political openness during the early phase of his presidency. Employing a qualitative approach and Robert Entman’s framing analysis model, this research examines news coverage from six major media outlets — Kompas, Detik.com, IDN Times, Narasi, Liputan6, and TVOne — focusing on four framing dimensions: problem definition, causal diagnosis, moral evaluation, and treatment recommendation. The findings reveal a notable consensus across media in defining the core problem as a deficit in direct and transparent presidential communication on strategic national issues, with causes attributed to one-way and intermediary-based communication practices. However, variations emerge in moral judgments and proposed solutions, reflecting each outlet’s ideological orientation, editorial stance, and audience segmentation. While Kompas and Narasi adopt a more critical-constructive position emphasizing inclusivity and sustainability, IDN Times, Liputan6, and TVOne frame the dialogue more affirmatively as democratic progress, and Detik.com maintains a pragmatic and neutral tone. This study demonstrates that media framing of political dialogue is not neutral but constitutes a site of meaning contestation shaped by power relations. The findings contribute to political communication scholarship by highlighting how media simultaneously reproduce power narratives and perform a constrained watchdog role within Indonesia’s procedural democracy.